Degree major, usage duration, and price as determinants of students' decision to buy, borrow, or ignore G.E. courses recommended reading titles - Razon, Ma. Sharon J., 1977- (Institute of Library Science, University of the Philippines Diliman, 2001)
In the competent world of tertiary education, it is the responsibility of college students to read in order to pass their courses. Reliable reading materials are those recommended by professors by which pointers are taken for class lectures, reports and examinations. With so many reading materials recommended to students, how do the students access the materials?